CompTIA cybersecurity analyst (CSA+) study guide: exam CS0-001 - Mike Chapple, Chapple; David Seidl, Seidl (Sybex, 2017)
NOTE: The name of the exam has changed from CSA+ to CySA+. However, the CS0-001 exam objectives are exactly the same. After the book was printed with CSA+ in the title, CompTIA changed the name to CySA+. We have corrected the title to CySA+ in subsequent book printings, but earlier printings that were sold may still show CSA+ in the title. Please rest assured that the book content is 100% the same.Prepare yourself for the newest CompTIA certification The CompTIA Cybersecurity Analyst+ (CySA+) Study Guide provides 100% coverage of all exam objectives for the new CySA+ certification. The CySA+ certification validates a candidate's skills to configure and use threat detection tools, perform data analysis, identify vulnerabilities with a goal of securing and protecting organizations systems. Focus your review for the CySA+ with Sybex and benefit from real-world examples drawn from experts, hands-on labs, insight on how to create your own cybersecurity toolkit, and end-of-chapter review questions help you gauge your understanding each step of the way. You also gain access to the Sybex interactive learning environment that includes electronic flashcards, a searchable glossary, and hundreds of bonus practice questions. This study guide provides the guidance and knowledge you need to demonstrate your skill set in cybersecurity. Key exam topics include: Threat management Vulnerability management Cyber incident response Security architecture and toolsets